Metastatic renal cell carcinoma presenting as a duodenal mass. Issue 7 (22nd July 2022) - Vrakas, Spyridon; Skouloudis, Epameinondas; Koutoufaris, Georgios; Manoloudaki, Kassiani; Karapiperis, Dimitrios; Xourgias, Vasilis
Abstract: We report a case of renal cell carcinoma metastasis to the duodenum. Abstract : Renal cell carcinoma (RCC) is a common cause of cancer‐related mortality worldwide. It rarely affects the gastrointestinal tract and should be considered in the differential diagnosis in patients with iron deficiency anemia, a mass in the GI tract, and a history of RCC.